Subsurface Drilling and Geomechanic Properties at Taman Pudu Ulu, Cheras, Kuala Lumpur - bin Razani, Ahmad Hilmi (Universiti Teknologi PETRONAS, 2014)
This project is about a subsurface study of Taman Pudu Ulu, Cheras, Kuala Lumpur with emphasized of Geomechanic properties. Subsurface drilling and seismic data were used to understand the subsurface condition of the study area such as the type and thickness of the strata. 4 boreholes were drilled and a seismic line is shot in the study area. Borehole and soil samples were recovered to know Geomechanic properties of the area by conducting experiments such as soil bulk density and specific gravity. From these two experiments, we can use the finding and calculate the strain. Taman Pudu Ulu overlies the Kuala Lumpur Limestone formation that is known for its karstic features such as caves and cavities. Hence by knowing the Geomechanic properties such as the normal strain and shear strain we can plan a safer and economics construction that is plan at the area in the future.